SELECTION OF PROTOCOL FOR IP-TELEPHONY NETWORK CONSTRUCTION - Дубчак, О. В.; Петраш, І. Б. (Science-based technologies, 2016)
The current state of IP telephony is considered in this article. It is presented popular SIP and H.323 protocols. Advantages and disadvantages each of them were estimated. Schemes of network IP telephony by using protocols were depicted. A question is raised about a transmission of voice data confidentiality and integrity, availability of information. It is indicated that H.323 allows more efficient uses of ISDN technology by using H.320 with fewer lines of ISDN. The report states that both protocols provide a good network scalability, but H.323 protocol is more complicated due to the number of requests and the binary representation of messages. The main advantages of SIP protocol include a simplicity of organization, mobility, extensibility. A range of services provided by both protocols is approximately the same, which implies the possibility to use both protocols simultaneously. On the other hand, a comparative analysis of the protocols was conducted and concluded on SIP protocol compliance task of building integrated and mixed networks.